Growth, Structural and Optical Characterization of ZnO Nanotubes on Disposable-Flexible Paper Substrates by Low-Temperature Chemical Method. (28th June 2012) - Soomro, M. Y.; Hussain, I.; Bano, N.; Lu, Jun; Hultman, L.; Nur, O.; Willander, M.
Abstract : We report the synthesis of vertically aligned ZnO nanotubes (NTs) on paper substrates by low-temperature hydrothermal method. The growth of ZnO NTs on the paper substrate is discussed; further, the structural and optical properties are investigated by scanning electron microscope (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy (EDS), and cathodoluminescence (CL), and it was found that the ZnO NTs on paper substrate fulfill the structural and optical properties of ZnO NTs grown on other conventional substrates. This will be more beneficial in future usage of ZnO NTs in different fields and applications. Particularly, this approach opens the ways in research and development for high volume manufacturing of low-cost, flexible optoelectronics devices on disposable paper substrates and can be used in the future miniaturization trends.